2020
DOI: 10.1136/bmjopen-2020-037053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of major lower limb amputation using routinely collected electronic health data in the UK: a systematic review protocol

Abstract: IntroductionIt is estimated that peripheral arterial disease occurs in one in five people aged over 60 years in the UK. Major lower limb amputation is a debilitating and life-changing potential outcome of peripheral arterial disease. A number of risk factors are involved in the development of the disease including smoking and diabetes. There is debate over the prevalence of major lower limb amputation in the UK with regional variations unexplained. The choice of data source can affect the epidemiological calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…When conducting a systematic review on the reasons for variation in reported incidence of major lower limb amputation [ 16 , 17 ], a major issue was the overlap of study period. Data syntheses including whole country population studies may mean combining studies with a major participant overlap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When conducting a systematic review on the reasons for variation in reported incidence of major lower limb amputation [ 16 , 17 ], a major issue was the overlap of study period. Data syntheses including whole country population studies may mean combining studies with a major participant overlap.…”
Section: Resultsmentioning
confidence: 99%
“…Various aspects of double-counting of populations in included observational and real-world evidence studies in meta-analysis, henceforth referred to as the overlapping populations problem for brevity, will be discussed with case-studies used to highlight particular issues. The case studies used to illustrate the common issues with overlapping populations have been identified through involvement of authors of this manuscript with multiple applied synthesis projects [15][16][17][18]. Each case study has utilised various approaches of addressing the problem; in each scenario the method used to address this issue by authors was discussed, which considered the most appropriate approach to answer the research question and maximise the data available.…”
Section: Methodsmentioning
confidence: 99%
“…Metaanalysis of incidence/prevalence and meta-regression of time trends using a random effects model were planned but not performed as extracted data were not suitable for pooling. 19 Patient and public involvement Patients or the public were not involved in the design, or conduct, or reporting, or dissemination plans of our research.…”
Section: Data Synthesismentioning
confidence: 99%
“…[ 17 , 18 , 19 , 20 , 21 ]. Studies show that approximately 90% of amputation cases involve the lower limbs, and the incidence of these amputations in Europe has increased considerably in the last 25 years, ranging from 180–200 patients to 1 million and it is estimated that this negative dynamic will continue in the coming 15–20 years [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%